Pilomyxoid astrocytoma of the brainstem - Pereira, Francisco Otavio [UNESP]; Lombardi, Ismael Augusto [UNESP]; Mello, Adriana Yuki [UNESP]; Romero, Flavio Ramalho [UNESP]; Ducati, Luis Gustavo [UNESP]; Gabarra, Roberto Colichio [UNESP]; Zanini, Marco Antonio [UNESP] (SAGE Publications, 2013)
A pilomyxoid astrocytoma is a recently described tumor that occurs predominantly in the hypothalamic-chiasmatic region and is rarely found elsewhere. It has similar features as pilocytic astrocytomas, but has distinct histological characteristics and a poorer prognosis. A pilomyxoid astrocytoma is an aggressive tumor, and increased awareness is necessary with a suspect case. We present the first case of a pilomyxoid astrocytoma of the brainstem described after the newest World Health Organization classification of central nervous system tumors. © F.O. Pereira et al., 2013. Licensee PAGEPress, Italy.
Keywords: Brain tumor; Pediatric; Pilomyxoid astrocytoma; glial fibrillary acidic protein; abducens nerve paralysis; astrocytoma; ataxia; brain stem pilomyxoid astrocytoma; brain stem tumor; case report; child; diplopia; female; gait disorder; histopathology; human; human tissue; Karnofsky Performance Status; neurologic examination; neurosurgery; nuclear magnetic resonance imaging; postoperative period; proton nuclear magnetic resonance; reoperation; school child